The key role of prefrontal cortex structure and function - Brase, Gary L.; Raffone, Antonino (My University, 2006)
The tension between focusing on species similarities versus species differences (phylogenetic versus adaptationist approaches) recurs in discussions about the nature of neural connectivity and organization following brain expansion. Whereas Striedter suggests a primary role for response inhibition, other possibilities include dense recurrent connectivity loops. Computer simulations and brain imaging technologies are crucial in better understanding actual neuronal connectivity patterns
Commentary on target article
Keywords: Working memory; Complexity